Web-Based Souvenir Ordering Information System for Pasuruan: Sistem Informasi Pemesanan Oleh – Oleh khas Pasuruan Berbasis Web - Ansa, Mochamad Musaddat; Astutik, Ika Ratna Indra (Indonesian Journal of Innovation Studies, 2022)
Dry Bakpia is a typical food from Pasuruan city made from green beans. One place that produces bakpia in a simple and conventional way is a new bakpia shop. In a survey conducted by the new bakpia shop, they still use the manual system, at this time the new bakpia shop is experiencing difficulties in selling production.The Covid-19 pandemic has an impact on all sectors, including business actors or MSMEs. For this reason, a final project or thesis entitled "Sales Information System By - By Pasuruan is made", so that it can still serve the sale of souvenirs via online. The system is made using the waterfall method, the programming language used is PHP with SQL database. The results obtained in the form of a web-based sales system.